Mite (Acari; Arachnida) diversity of two native plants in fragments of a semideciduous seasonal forest in Brazil - Demite, Peterson R.; Lofego, Antonio C. [UNESP]; Feres, Reinaldo J. F. [UNESP] (Taylor & Francis, 2013)
Studies to determine mite species richness in natural environments are still scarce, and have been conducted mainly in tropical ecosystems. The aim of this study was to determine the species richness of mites on two common native plants in fragments of the semideciduous seasonal forest in the Northwest of São Paulo State, Brazil. In each of eight fragments, 10 specimens of Actinostemon communis (Euphorbiaceae) and 10 of Trichilia casaretti (Meliaceae) were selected and marked. In total, 124 species of mites belonging to 21 families were found on the two plants. Tarsonemidae had the highest diversity (34 species), followed by Phytoseiidae (31), Tetranychidae (9) and Tenuipalpidae (8). Species accumulation curves for the two sampled plants did not reach an asymptote, even with the large sampling effort. Hence, it is estimated that a greater sampling effort may lead to an increase in species richness compared with what was found in this study. The richness of this mite fauna suggests that preservation of these plant species is important to maintain the mite diversity in these forest fragments. © 2013 Taylor & Francis Group, LLC.
Keywords: Atlantic Forest; biodiversity; Euphorbiaceae; Meliaceae; mite fauna